Membangun Plot Twist Reverse Chronology dengan Menggunakan Teori Inner Conflict dalam Skenario Film Fiksi “Pulang” - Aryananda Putra; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The movie "Pulang" presents a story that uses the theory of inner conflict in building a reverse chronology plot, to describe the emotional journey of the main character Karin, who must overcome and accept inner conflict triggered by dissociative amnesia due to trauma experienced by her mother 2 years ago. By introducing the audience to Karin's life, which is characterized by sincerity and patience in taking care of her mother despite not being considered a child by her own mother due to amnesia, this film uses the theory of inner conflict in the mother character. Through the inner conflict theory, it can build a reverse chronology plot twist. Through the reverse chronology plot twist, the audience is invited to explore the past of Rama and his mother, detailing the traumatic event that resulted in the amnesia. The combination of inner conflict and plot twist reverse chronology in the context of trauma and amnesia creates a story that is full of pain, full of inner struggle, and is able to arouse empathy from the audience towards the complexity of humans in dealing with past wounds.